The Effect Of Capital Intensity, Inventory Intensity, Multi-nationality, And Leverage On Tax Avoidance Practices - Achmad Awaludin Agam Mudi Firmansyah; Rahman, Aulia Fuad (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
Tax avoidance is a legal strategy for minimizing corporate income tax obligations by exploiting loopholes in tax regulations. This study examines the effect of capital intensity, inventory intensity, multinationality, and leverage on tax avoidance, which was proxied by the Long-Run Cash Effective Tax Rate (CETR). From a population of 125 consumer non-cyclical manufacturing companies listed on the Indonesia Stock Exchange during the 2018–2023 period, 54 were selected as the samples through purposive sampling. Multiple linear regression was applied to the panel data, processed using EViews 12. The T-test results indicated that capital intensity, inventory intensity, and leverage each had a positive effect on tax avoidance, while multinationality had no effect. Moreover, the F-test results showed that capital intensity, inventory intensity, multinationality, and leverage collectively influenced tax avoidance.